Are Virtual Objective Assessments of Fall‐Risk Feasible and Safe for People with Parkinson's Disease?. Issue 6 (4th July 2022) - Afshari, Mitra; Hernandez, Andrea V.; Nonnekes, Jorik; Bloem, Bastiaan R.; Goetz, Christopher G.
Abstract: Background: Falls are inherent to Parkinson's disease (PD) progression, and risk assessment is mandatory for optimal long term management. Objective: To determine if the telehealth application of two observer‐based, objective measures of fall‐risk in PD— Five‐Times‐Sit‐To‐Stand (FTSTS) and 360° Rapid‐Turns‐Test (RTT)—is feasible and safe. Methods: Following in‐clinic training, 15 people with Hoehn and Yahr Stage 2 (n = 8) and 3 (n = 7) PD, median MoCA score 25 (range 14–29), and subjective freezing‐of‐gait (n = 13), participated in four televisits with care partners biweekly for 10 weeks where virtual FTSTS/RTT assessments were performed. Results: Participants completed all protocol‐driven 120 virtual FTSTS and 60 RTT assessments with effective ratability (feasibility) and zero adverse events (safety). 22% virtual FTSTS and 55% RTT met criteria for high fall‐risk designation. Conclusions: Objective fall‐risk assessment with virtual FTSTS and RTT through telehealth among HY2‐3 PD patients, with varying motor and cognitive function, is feasible and safe following introductory in‐clinic training.